Characterization of lbpA, the structural gene for a lactoferrin receptor in Neisseria gonorrhoeae. - Biswas, G D (1995)
Neisseria gonorrhoeae acquires iron (Fe) efficiently from lactoferrin (LF). A 103-kDa gonococcal outer membrane LF-binding protein (Lbp) was identified previously. We isolated the structural gene lbpA for Lbp1 by screening a gonococcal library for a clone that could repair an LF- receptor mutant. An mTnCm3 transposon insertion mutant of lbpA was unable to use LF-bound Fe for growth, unable to bind LF to whole cells, and unable to express Lbp1. The DNA sequence of lbpA predicted a protein that shared 94% identity with the meningococcal LF receptor protein, Lbp, and was closely related to Tbp1, one of the transferrin receptor proteins. Clinical isolates of gonococci are frequently unable to acquire Fe from LF, and LF- isolates do not have a functional LF receptor. The wild-type lbpA gene transformed most tested LF- clinical isolates to LF+, indicating that lbpA is defective in many clinical isolates.